SEKOLAH UMUM BERBASIS ISLAM DI SMA UNGGULAN Haf-Sa ZAINUL HASAN GENGGONG - Umi Fatimah; Izzatul Amaliah; Fitrianingsih (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
In Indonesia today we find many Islamic-based schools, not only Islamic with their madrasahs, but many religious educational institutions such as Christianity, Catholicism, Hinduism and Buddhism which have schools where religious values ​​form the basis. learning process. Along with the development of religious education in public schools, attention to madrasas or Islamic education in general has occurred since the Central Indonesian National Committee Working Committee (BPKNIP) in the post-independence period issued an edict and proposed education or teaching in mushollah, surau, mosques and madrasas to continue. and improved”. Madrasa in the form we know today literally comes from Arabic which means the same or equivalent to the Indonesian word "school" (school). Madrasa here then has a specific connotation, where children can get religious lessons. Madrasas were what was previously called religious education in the form of learning to recite the Qur'an, then adding practical worship lessons, continuing to teach monotheism, hadith, interpretation, Islamic dates in Arabic. Then also entered general lessons and skills. In terms of educational level, at first the madrasa was synonymous with learning to recite the Koran, the basic level of study of the book and further study of the book, then changed to the level of Elementary Madrasah, Tsanawiyah Madrasah, and Aliyah Madrasah. This research was conducted with the aim of finding important variables that have a background in the development of Islamic-based public school education. This study uses a case study method (Case Study) which is qualitative in nature in discussing the characteristics of Islam as an institutional identity at SMA Haf-Sha Unggulan Zainul Hasan Genggong by using interview, observation, and documentation research techniques. This research was started from November 27 to December 13 2022 at Haf-Sha Unggulan Zainul Hasan Genggong High School which is located at Gerojokan Kulon Village, Pajarakan District, Probolinggo Regency, East Java Province.